PENGAWASAN DINAS PERINDUSTRIAN DAN PERDAGANGAN KOTA PEKANBARU DALAM PEREDARAN DAN PENJUALAN MINUMAN BERALKOHOL BERDASARKAN PERATURAN MENTERI PERDAGANGAN REPUBLIK INDONESIA NOMOR 20/M- DAG/PER/4/2014 TENTANG PENGENDALIAN DAN PENGAWASAN TERHADAP PENGADAAN,PEREDARAN DAN PENJUALAN MINUMAN BERALKOHOL - Siti Hartinah; Mexsasai Indra; Ledy Diana (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
Supervision of the distribution and sale of alcoholic beverages in PekanbaruCity really needs to be carried out in an orderly manner with the aim ofprotecting the public from drinking drinks that are intoxicating and are not verygood for human consumption. Alcoholic drinks may be traded in accordance withthe provisions set by the government as stated in the Regulation of the Minister ofTrade of the Republic of Indonesia Number 20/M-Dag/Per/4/2014 concerningControl and Supervision of the Procurement, Distribution and Sales of AlcoholicBeverages.This type of research is sociological legal research, which is research thatwants to see the correlation between law and society, so as to be able to revealthe effectiveness of the enactment of law in society and identify unwritten lawsthat apply to people in the field or to society. The data sources used are primarydata and secondary data which consist of primary legal materials, secondarylegal materials, and tertiary legal materials. The data collection technique in thisstudy is by observation, interview, literature review. After the data is collected, itis then analyzed to draw conclusions.From the results of the study it was concluded that, First, Supervision of thePekanbaru City Industry and Trade Service in the Circulation and Sales ofAlcoholic Beverages has not been carried out properly. Second, the inhibitingfactors in carrying out Supervision of the Distribution and Sales of AlcoholicBeverages are due to the lack of raids, the lack of community participation, lawenforcement factors and the absence of regional regulations on liquor inPekanbaru City, This is due to the lack of public awareness regarding thenegative impacts of liquor and the lack of strict regulations regarding liquor inPekanbaru City.Keywords: Inhibiting Factors - Alcoholic Beverages - Monitoring